THE EFFECT OF EDUCATION LACTATION ON BREASTFEEDING BEHAVIOR INFANT 0-6 MONTHS IN KENDARI INDONESIA - Nurmiaty, Nurmiaty; Arsin, Arsunan A.; Sirajuddin, Saifuddin; Syafar, Muh (Public Health of Indonesia, 2016)
Background: Provision of breast milk (ASI) is important because it lowers the risk of morbidity and mortality in infants. Breast milk is the ideal food for a baby's growth and development from birth to age 6 months. Thus, the appropriate interventions to improve the behavior of exclusive breastfeeding is really needed.Aim: To determine the effect of education lactation on behavior breastfeeding for infants 0-6 months.Methods: This was Quasy Experiment study with pre-test and post-test design with control group. Samples mother (gestational age â‰¥28-32 weeks) were divided into 3 groups: 1) those who received education lactation and a modification module (n = 21), 2) a group that only received a modification module (n = 21) and 3) a group that only received the MCH book (n = 20). Data were collected using a questionnaire, the implementation of the pre-test before starting lactation education, the first post-test after the intervention with a lag time of 2 months and the second post-test after the intervention with a lag time of 3 months.Results: There had been an increase of knowledge and attitude scores in each group and the highest in the group 1. At the age of 0-3 months, there was a difference in breastfeeding in all groups. In the sixth month, there was a change in group 2, while group 3 had no change, but some mothers given partially breastfed and formula. The tendency of increasing age of the baby causes mothers to give formula milk, but in group 1, majority of women still gave exclusive breastfeeding until the baby 6 months old. It was shown that there was an influence of  lactation education on behavior of breastfeeding infants 0-6 months.Conclusion: Education lactation can improve  knowledge, attitudes and behavior of mother to give breastfeeding up to 6 months.